2016
DOI: 10.1007/s13197-016-2293-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and starch characteristics of milled rice from different cultivars affected by transplantation date

Abstract: The effects of transplantation date on milled rice (physicochemical, amino acids composition and protein profiling) of different cultivars and their starch characteristics (granules size distribution, pasting and thermal) were investigated. Head rice yield increased (2.0-4.1 %) and chalky grains (5-10 %) decreased with delaying the paddy transplantation of different cultivars by 20 days. Delayed transplantation of paddy significantly increased asparagine, glutamine, threonine, cysteine, methionine, tryptophan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Pasting parameters were determined with a Rapid Visco Analyzer (RVA) (Model RVA 3D+, Newport Scientific Australia) as described by Kaur et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Pasting parameters were determined with a Rapid Visco Analyzer (RVA) (Model RVA 3D+, Newport Scientific Australia) as described by Kaur et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…The varieties exhibited lower BV suggesting their lower amylose content. It has been reported that variation in amylose content and PC depends on different environmental conditions during day and nighttime as reported by (Kaur, Pal et al., ). IPV showed higher BV as compared to TPV, except PR127.…”
Section: Resultsmentioning
confidence: 86%
“…IPV alone can add 20%–25% to increased productivity, even if other components of production remain the same which is valuable for farmers and consumers for future use. Physicochemical characteristics of rice are dependent on the variety type, genetic background, and environmental conditions during the development stage of grain filling (Kaur, Pal et al., ). Rice protein has well‐balanced amino acid profiles having higher lysine content as compared to wheat, corn, millet, and sorghum (Hegsted, ) which has a great potential to improve human nutrition in rural families in Asia and become a major objective of rice breeding.…”
Section: Introductionmentioning
confidence: 99%
“…This is most probably due to cross reactivity of other rice proteins that may have co-purified with gliadin in the extraction procedure. 42,43 The findings of this study could potentially be used to produce wheat-like rice. To achieve this goal, all three genes (gliadin, LMW and HMW glutenin) have to be expressed in a single rice plant.…”
Section: Discussionmentioning
confidence: 96%